2008
DOI: 10.1080/00498250802499459
|View full text |Cite
|
Sign up to set email alerts
|

Toward an improved prediction of humanin vivobrain penetration

Abstract: The penetration of drugs into the central nervous system is a composite of both the rate of drug uptake across the blood-brain barrier and the extent of distribution into brain tissue compartments. Clinically, positron emission tomography (PET) is the primary technique for deriving information on drug biodistribution as well as target receptor occupancy. In contrast, rodent models have formed the basis for much of the current understanding of brain penetration within pharmaceutical Drug Discovery. Linking thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 71 publications
6
59
0
Order By: Relevance
“…Wan et al (2007) showed that rat and mouse brain fraction unbound had good correlation (R 2 ϭ 0.9887, n ϭ 25). Summerfield et al (2008) observed that brain fraction unbound among rat, Landrace pig, and human correlated well (R 2 Ͼ 0.9, n ϭ 21). In a review article, Read and Braggio (2010) reported that brain fraction unbound was conserved in eight species (dog, cynomolgus monkey, guinea pig, rat, man, marmoset, pig, and mouse) using a limited number of test compounds (seven compounds).…”
Section: Introductionmentioning
confidence: 87%
“…Wan et al (2007) showed that rat and mouse brain fraction unbound had good correlation (R 2 ϭ 0.9887, n ϭ 25). Summerfield et al (2008) observed that brain fraction unbound among rat, Landrace pig, and human correlated well (R 2 Ͼ 0.9, n ϭ 21). In a review article, Read and Braggio (2010) reported that brain fraction unbound was conserved in eight species (dog, cynomolgus monkey, guinea pig, rat, man, marmoset, pig, and mouse) using a limited number of test compounds (seven compounds).…”
Section: Introductionmentioning
confidence: 87%
“…Quantification of a drug's plasma protein binding [and hence fraction unbound in plasma (fup)] is essential for extrapolation of preclinical efficacy data, prediction of in vivo clearance from in vitro data, and estimation of free drug concentration in tissues (Kalvass and Maurer, 2002;Summerfield et al, 2008;He et al, 2009). Interspecies differences in plasma protein binding (PPB) need to be considered for prediction of volume of distribution and clearance in humans (Benet and Hoener, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this approach the unbound fraction in brain tissue is estimated by the unbound fraction in brain homogenate, which is determined using equilibrium dialysis or ultracentrifugation. Several indirect validation studies have been published, such as comparing the projected brain to plasma concentration ratios with the observed ratios, or comparing the unbound brain fraction determined by brain homogenate method with that determined by brain slice method, or by CSF method (Kalvass and Maurer, 2002;Maurer et al, 2005;Becker and Liu, 2006;Liu et al, 2006;Summerfield et al, 2006Summerfield et al, , 2008. Recently, Fridén et al (2007) showed that C ub predicted C m within 3-fold of error for 10 of 15 compounds.…”
mentioning
confidence: 99%